The Impact of Using Information Technology on Improving Employee Performance A Study on A Sample of Government Banks - Mahmood, Tahreer; Atiyah, Yousif (Indonesian Journal Publisher, 2026)
This research aims to study the impact of information technology (IT), with its key indicators—hardware, software, networks, and databases—on improving employee performance within government banks. The importance of this topic stems from the increasing role of technology in supporting banking operations and enhancing operational efficiency and the quality of services provided to customers. The study adopted a descriptive-analytical approach to diagnose the availability and use of these indicators and to determine their impact on job performance elements such as productivity, accuracy, commitment, and speed of completion. The study concluded that modern devices contribute to accelerating banking operations and reducing technical malfunctions, while banking software plays a pivotal role in enhancing consistency and accuracy in processing financial data. The results also showed that stable and high-speed networks are essential for ensuring smooth workflow and information exchange within and between branches, while organized and secure databases improve the quality of operational and administrative decisions by enhancing access to and processing of information. The results indicated a significant and positive impact of all these indicators on improving employee performance. Employees using modern hardware and software and working within an efficient network environment demonstrated higher levels of efficiency and accuracy in completing tasks. The study also showed that continuous training on technological systems contributes to maximizing the benefits of the digital infrastructure, despite the persistence of some challenges related to inadequate maintenance or slow network speeds in certain government branches.